The Effectiveness of hCG and LHRH in Boys with Cryptorchidism: A Meta-Analysis of Randomized Controlled Trials - Bu, Q.; Pan, Z.; Jiang, S.; Wang, A.; Cheng, H. (Hormone and Metabolic Research, 2016)
To systematically review the efficacy of hCG and LHRH on testicular descent in boys with cryptorchidism, comprehensive search was performed to identify randomized controlled trials (RCTs) in PubMed, EMBASE, the Cochrane Library, Wanfang Database, and China National Knowledge Infrastructure (CNKI) up to March 2014. Outcomes included testicular complete descent rate (TCDR) and cure rate of patients. Study quality was evaluated using the Jadad scale. Meta-analysis was performed using Review Manager software. Finally, 13 studies were included. hCG and LHRH increased TCDR comparing with control group. The success rate of hCG and LHRH was 24 and 19%, respectively. Further, hCG and LHRH had signiﬁcant effect on bilateral cryptorchidism, but not on unilateral cryptorchidism. All side effects were transitory and not severe, but if they have long-term harms were not clear. hCG and LHRH can effectively increase TCDR and there was no significant difference between them. However, the hormones cannot be recommended for everyone because of their low success rates and potential long-term harms. Further studies are needed to determine the efficacy of hormonal treatment for subtypes of cryptorchidism.
Keywords: hormone; undescended testicle; systematic review